The Implementation Analysis of Clinical Governance by the Medical Committee at Deli Serdang Hospital - Ratna Wulandari; Zulfendri; Surya Utama (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Clinical governance aims to maintain and improve the quality of medical services for patients and protect patients from the risk of unexpected events as regulated in Law Number 44 of 2009 concerning Hospitals and Minister of Health Regulation Number 755 / MENKES / PER / IV / 2011 regarding the implementation medical committee at the hospital. The medical committee is one of the hospital's instruments that has an important role in implementing clinical governance so that the medical staff at the hospital is maintained professionally. In implementing clinical governance in hospitals, it is done by carrying out credentials, monitoring the quality of the medical profession, and maintaining the ethics and discipline of the medical profession. This type of research is qualitative in-depth interviews. Informants were selected using a purposive technique. The subjects in this study were informants relating to the medical committee. The results showed that the implementation of clinical governance in Deli Serdang Hospital was not going well. This can be seen from the implementation of medical committee activities that are not in accordance with the Minister of Health Regulation No. 755 / MENKES / PER / IV / 2011 concerning the implementation of medical committees in hospitals. The work program carried out by the medical committee at Deli Serdang Hospital is deemed not in accordance with the expected target. This is due to the lack of planning and budget that supports the implementation of clinical governance in Deli Serdang Hospital. The implementation of clinical governance by the medical committee in medical services at Deli Serdang Hospital has not been running well. Thus, good planning and budgeting is needed to strengthen the activities of the medical committee in achieving good clinical governance in Deli Serdang Hospital.